An Outline of the National Archives and Library of Ethiopia - Hryćko, Katarzyna (Aethiopica, 2007)
Ethiopia is a country of a centuries-old tradition and history of writing. It possessed its own unique system for gathering materials of historical importance and a pecular library system. Throughout the years manuscripts were kept under the custody of Ethiopian Church monks. In the 20th century Ethiopia’s succesive rulers attached great importance to the building of a European style central repository of all written materials. They established and gradually developed the National Archives and Library of Ethiopia (NALE). The paper outlines the history of NALE from its beginnings up to now.